A microfluidics-based method for culturing osteoblasts on biomimetic hydroxyapatite. (June 2021) - Atif, Abdul Raouf; Pujari-Palmer, Michael; Tenje, Maria; Mestres, Gemma
Abstract: The reliability of conventional cell culture studies to evaluate biomaterials is often questioned, as in vitro outcomes may contradict results obtained through in vivo assays. Microfluidics technology has the potential to reproduce complex physiological conditions by allowing for fine control of microscale features such as cell confinement and flow rate. Having a continuous flow during cell culture is especially advantageous for bioactive biomaterials such as calcium-deficient hydroxyapatite (HA), which may otherwise alter medium composition and jeopardize cell viability, potentially producing false negative results in vitro . In this work, HA was integrated into a microfluidics-based platform (HA-on-chip) and the effect of varied flow rates (2, 8 and 14 µl/min, corresponding to 0.002, 0.008 and 0.014 dyn/cm 2, respectively) was evaluated. A HA sample placed in a well plate (HA-static) was included as a control. While substantial calcium depletion and phosphate release occurred in static conditions, the concentration of ions in HA-on-chip samples remained similar to those of fresh medium, particularly at higher flow rates. Pre-osteoblast-like cells (MC3T3-E1) exhibited a significantly higher degree of proliferation on HA-on-chip (8 μl/min flow rate) as compared to HA-static. However, cell differentiation, analysed by alkaline phosphatase (ALP) activity, showed low values in both conditions. This study indicates that cells respond differently when cultured on HA under flow compared to static conditions, which indicates the need for more physiologically relevant methods to increase the predictive value of in vitro studies used to evaluate biomaterials. Statement of significance: There is a lack of correlation between the results obtained when testing some biomaterials under cell culture as opposed to animal models. To address this issue, a cell culture method with slightly enhanced physiological relevance was developed by incorporating a biomaterial, known to regenerate bone, inside of a microfluidic platform that enabled a continuous supply of cell culture medium. Since the utilized biomaterial interacts with surrounding ions, the perfusion of medium allowed for shielding of these changes similarly as would happen in the body. The experimental outcomes observed in the dynamic platform were different than those obtained with standard static cell culture systems, proving the key role of the platform in the assessment of biomaterials. Graphical abstract: Image, graphical abstract